Mergers and acquisitions : Pernod Ricard and Beam - Boquinhas, David Jorge Martins (2014)
The spirits industry is consolidating with more than 40 M&A deals in 14 years. Organic growth is not the only priority major players have. In order to maintain their position on top, big producers and marketers of spirits have long been following a regular strategy of acquisitions and divestitures that allows them to create value for shareholder. In this study, an overview of a potential deal between Pernod Ricard S.A. and Beam Inc. is conducted by taking into consideration this deal’s place within the academic literature on Valuation and M&A, this industry and companies’ characteristics and value drivers, and how these are reflected in the assessment of value creation from the deal. According to the study’s conclusion, Pernod Ricard and Beam could create value for its shareholders by merging in a debt financing deal that would involve Pernod paying a 19% premium over last year average share price of Beam, which in turn would generate net synergies corresponding to around 8% of Pernod current enterprise value. The study concludes with further insights on how this deal could generate more value, and how different conditions could affect the viability of the merger.